Highly polarised gamma photons from electron-laser collisions - S. Tang; B. King; H. Hu (Physics Letters B, 2020)
We detail a method to produce a GeV-photon source with polarisation degree exceeding 91% and 78% (corresponding to a 96% and 89% fraction of the photons) for linear and circular polarised photons respectively and with a brilliance of the order of 1021photons/(smm2mrad20.1%BW). Using currently available multi-GeV electron bunches and laser pulses of moderately relativistic intensities, we show how the weakly nonlinear regime can produce photons polarised mainly parallel to the laser field. We demonstrate the robustness of this scheme by considering electron bunches of various emissivities colliding with linearly and circularly-polarised laser pulses at a range of angles.